اردوناولٹ میں اخلاقی ومعاشرتی مسائل کی عکاسی: Reflection of Moral and Social problems in Urdu Novelt (Al-Qamar, 2022)
Urdu novelettes have played a crucial role in addressing moral and social issues in the sub-continent, particularly the challenges faced by the weak and middle class. These literary works have highlighted the unjust division of wealth and the dominance of certain sections of society, leading to economic, moral, and social crises. They have shed light on social evils, such as corruption and gender inequality, and have offered solutions and alternative values. Through compelling narratives, Urdu novelettes have created awareness, stimulated discussions, and advocated for positive change in society.
Keywords: Moral and Social issue; Economy Crises; Feudalism System; Poverty; hunger